Multilayer structure comprising insulating layer
By using olefin-aromatic vinyl compound-aromatic polyene copolymer and surface modifier in the insulating layer, and combining with a specific resin layer, the problem of insufficient bonding strength on the smooth surface of the copper foil is solved, and high Low dielectric properties and high bond strength in frequency multilayer substrates.
Patent Information
- Application Number
- CN202411678747.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2021-10-14
- Filing Date
- 2022-10-12
- Publication Date
- 2025-01-03
AI Technical Summary
The prior art is difficult to provide a high bonding strength insulating layer for the smooth surface of copper foil, especially in the interlayer insulating materials of high-frequency signal transmission lines, antennas and multi-layer substrates, when the insulating material is connected to the smooth surface of copper foil. Inadequate bonding strength.
Using an insulating layer containing an olefin-aromatic vinyl compound-aromatic polyene copolymer and a surface modifier, a resin layer combining polyimide, liquid crystal polymer, polyphenylene ether and a polyfunctional aromatic vinyl resin, Through a specific laminated structure and surface treatment, high bond strength between the insulating layer and the smooth surface of the copper foil is achieved.
It realizes high bonding strength between the insulating layer with low dielectric constant, low dielectric loss tangent and low water absorption rate and the smooth surface of copper foil. It is suitable for high-frequency multi-layer substrates, improving the performance of interlayer insulating materials.
Smart Images

Figure BDA0005147747820000261 
Figure BDA0005147747820000262 
Figure BDA0005147747820000271
Abstract
Description
[0001] This application is a divisional application of the Chinese invention patent application (PCT application number PCT / JP 2022 / 038065) with an application date of October 12, 2022, application number 202280057657.4, and invention name “Multilayer structure including insulating layer”. Technical Field
[0002] The present invention relates to a multilayer structure having an insulating layer formed of a composition having high adhesion to a smooth surface of a copper foil. Background Art
[0003] As the communication frequency develops towards the high frequency bands above the gigahertz band, the demand for multilayer substrates formed by CCL and FCCL containing insulating materials with low dielectric properties increases. Fluorine-based resins such as perfluoroethylene have excellent low dielectric constant, low dielectric loss and excellent heat resistance, but are difficult to form and process, and film formability. In addition, there are also problems in the adhesion with the copper foil of the wiring, so it is difficult to apply to multilayer substrates. On the other hand, substrates and insulating materials using post-curing resins such as epoxy resins, unsaturated polyester resins, polyimide resins, and phenolic resins are widely used because of their heat resistance and ease of operation, but the dielectric constant and dielectric loss are relatively high, and as insulating materials for high frequencies, it is expected to be improved (Patent Document 1).
[0004] Therefore, hydrocarbon resins with low dielectric properties in nature have attracted much attention. Originally, in order to make hydrocarbon resins as thermoplastic resins into curable resins, it is necessary to introduce functional groups, but generally speaking, functional groups that react with free radicals or perform thermal reactions have polarity, so low dielectric properties will deteriorate. When it is desired to introduce functional groups consisting only of hydrocarbons, such as aromatic vinyl, there are many cases of utilizing intermolecular reactions between expensive hydrocarbon monomers (patent document 2), which is not economical in many cases. Patent document 3 shows a solidified body, which is obtained by a specific coordination polymerization catalyst, and comprises ethylene-olefin (aromatic vinyl compound)-aromatic polyene copolymers and non-polar vinyl compound copolymers with specific composition and coordination. In the case of this technology, only one of the two vinyl groups of aromatic polyene (divinylbenzene) is selectively copolymerized and the remaining vinyl group is preserved, so it is possible to easily obtain hydrocarbon copolymer macromonomers with the functional group of aromatic vinyl. The solidified bodies obtained from the same olefin-aromatic vinyl compound-aromatic polyene copolymer and its composition with auxiliary raw materials have the characteristics of low dielectric constant and low dielectric loss tangent, and can be given a wide range of soft to hard properties by selecting the composition and appropriate auxiliary raw materials (Patent Documents 4 and 5). In addition, these materials can show high adhesion (bonding strength) with the roughened surface of copper foil as shown in the examples. Therefore, it is considered to be suitable for various substrate materials and insulating materials for high-frequency signals.
[0005] However, in particular, when used as a high-frequency transmission line such as a microstrip line, an antenna, an interlayer insulating material for a multilayer substrate, or a coverlay, the insulating material is in contact with the smooth surface of the copper foil, and a high bonding strength (peel strength) with the smooth surface of the copper foil is required. In particular, for interlayer insulating materials in the form of a sheet or a film, at least a portion or at least one side thereof is in contact with the smooth surface of the copper foil, and a high bonding strength with the smooth surface of the copper foil is required. However, in the disclosed patent documents, there is no disclosure of a technology for imparting high adhesion (bonding strength) to the smooth surface of the copper foil to the insulating material.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Laid-Open No. 6-192392
[0009] Patent Document 2: Japanese Patent Application Publication No. 2004-087639
[0010] Patent Document 3: Japanese Patent Application Publication No. 2007-217706
[0011] Patent Document 4: International Publication No. 2021 / 112087
[0012] Patent Document 5: International Publication No. 2021 / 112088 Summary of the invention
[0013] Problems to be solved by the invention
[0014] In view of the above-mentioned prior art, it is desired to provide a multilayer structure useful as a multilayer substrate having an insulating layer I (also described as "interlayer insulating material" in this specification) that exhibits high bonding strength with a copper foil smooth surface.
[0015] Means for solving problems
[0016] That is, in the present application, the following means for solving the above-mentioned problems can be provided.
[0017] Method 1.
[0018] A multilayer structure, characterized in that it comprises:
[0019] More than one insulating layer,
[0020] One or more resin layers, and
[0021] One or more copper foils having a smooth surface and a roughened surface,
[0022] In the multilayer structure,
[0023] The insulating layer comprises an olefin-aromatic vinyl compound-aromatic polyene copolymer and a surface modifier.
[0024] The resin layer comprises one or more selected from polyimide (PI), liquid crystal polymer (LCP), polyphenylene ether (PPE), multifunctional aromatic vinyl resin (ODV), epoxy resin, and the same composition as the insulating layer.
[0025] At least one surface of each of the insulating layers is bonded to the smooth surface of the copper foil.
[0026] Regarding each of the resin layers, at least one surface of the resin layer is bonded to the roughened surface of the copper foil and the resin layer is not bonded to the smooth surface of the copper foil, or both surfaces of the resin layer are not bonded to the copper foil.
[0027] Method 2.
[0028] A multilayer structure as described in method 1, wherein at least one surface of the insulating layer has a portion recessed in the stacking direction, and the copper foil is bonded in such a manner that the copper foil is accommodated in the recessed portion, thereby having a portion of the surface bonded to the smooth surface of the copper foil and another portion of the surface bonded to the resin layer.
[0029] Method 3.
[0030] The multilayer structure according to embodiment 1 or 2, wherein the surface modifier is a silane coupling agent.
[0031] Method 4.
[0032] The multilayer structure according to any one of Embodiments 1 to 3, wherein the olefin-aromatic vinyl compound-aromatic polyene copolymer satisfies all of the following conditions (1) to (4).
[0033] (1) The number average molecular weight of the copolymer is 500 or more and less than 100,000.
[0034] (2) The aromatic vinyl compound monomer is an aromatic vinyl compound having 8 to 20 carbon atoms, and the content of the aromatic vinyl compound monomer unit is 0 to 70% by mass or 0 to 98% by mass.
[0035] (3) The aromatic polyene is one or more selected from polyenes having a carbon number of 5 to 20 and having a plurality of vinyl and / or vinylidene groups in the molecule, and the content of vinyl and / or vinylidene groups derived from the aromatic polyene unit is 1.5 to less than 20 per unit number average molecular weight.
[0036] (4) The olefin is one or more selected from olefins having 2 to 20 carbon atoms, the content of the olefin monomer unit is 10% by mass or more, and the total of the olefin monomer unit, the aromatic vinyl compound monomer unit and the aromatic polyene monomer unit is 100% by mass.
[0037] Method 5.
[0038] The multilayer structure according to any one of aspects 1 to 4, wherein the insulating layer further includes one or more selected from the following (a) to (c).
[0039] (a) Curing agent
[0040] (b) one or more resins selected from hydrocarbon elastomers, polyphenylene ether resins, and aromatic polyene resins
[0041] (c) Polar monomers
[0042] Method 6.
[0043] The multilayer structure according to any one of aspects 1 to 5, wherein the content of the surface modifier in the insulating layer is 0.001 to 10 parts by mass based on 100 parts by mass of the olefin-aromatic vinyl compound-aromatic polyene copolymer.
[0044] Method 7.
[0045] The cured multilayer structure is formed by curing the multilayer structure according to any one of aspects 1 to 6.
[0046] Method 8.
[0047] A high-frequency transmission line, a multi-layer CCL substrate, a multi-layer FCCL substrate, an antenna or a cover layer, comprising the cured multi-layer structure described in method 7.
[0048] Effects of the Invention
[0049] In the present invention, a multilayer structure useful as a high-frequency multilayer substrate can be provided by bonding an insulating layer having low dielectric constant, low dielectric loss tangent, low water absorption and high insulation to a smooth surface of a copper foil with high bonding strength (peel strength). BRIEF DESCRIPTION OF THE DRAWINGS
[0050] [ Figure 1 ] shows the structure of the basic unit that may be contained in part or all of the multilayer structure according to the present invention.
[0051] [ Figure 2 ] shows specific examples of structures that may be included in part or all of the multilayer structure according to the present invention.
[0052] [ Figure 3 ] shows specific examples of structures that may be included in part or all of the multilayer structure according to the present invention.
[0053] [ Figure 4 ] shows a modified example of the above-mentioned basic unit. DETAILED DESCRIPTION
[0054] The multilayer structure comprises a copper foil, a resin layer bonded to the roughened surface of the copper foil, and an insulating layer bonded to the smooth surface of the copper foil (eg Figure 1 The multilayer structure may contain more than one such basic unit, or may contain a combination of the basic unit and other layers.
[0055] The insulating layer (one or more layers) included in the multilayer structure is a concept including interlayer insulating materials and covering layers. In addition, the so-called interlayer insulating material includes the concepts of interlayer adhesive materials and bonding sheets. The so-called sheet also includes the concept of film. In addition, in this specification, even if it is recorded as a film, it also includes the concept of sheet. The composition involved in the present invention is described in more detail below. In this specification, the so-called composition includes the concept of varnish. That is, the composition, especially the liquid composition, is recorded as varnish.
[0056] <Copper foil and roughened surface>
[0057] The copper foil (one or more) contained in the present multilayer structure can be any copper foil as long as it can be used in wiring and substrates. The thickness is not particularly limited, but is generally in the range of 1 to 500 μm, preferably 5 to 50 μm. It is preferably a copper foil that can cope with high frequencies, and can be a rolled copper foil or an electrolytic copper foil. The present copper foil has a roughened surface (also known as a matte surface, sometimes expressed as an M surface) and a smooth surface (glossy surface or polished surface, sometimes expressed as an S surface). For example, the surface roughness (maximum height) Rz of the roughened surface of the copper foil specified in JIS B0601:2001 is preferably 5 μm or less, particularly preferably 3 μm or less. For example, the surface roughness (maximum height) Rz of the roughened surface of the copper foil specified in JIS B0601:2001 is preferably greater than 0.5 μm. Such copper foil can be obtained from Furukawa Electric Co., Ltd., JX Metals Co., Ltd., Mitsui Mining & Smelting Co., Ltd., etc.
[0058] <Copper foil smooth surface>
[0059] The so-called smooth surface of the copper foil is a surface of the copper foil used for wiring and substrates that is not a roughened surface, and is a relatively smooth surface compared to the roughened surface. Generally speaking, the surface roughness (maximum height) Rz specified in JIS B0601:2001 of this smooth surface is 0.5 μm or less. As mentioned above, it is a relatively smooth surface compared to the roughened surface, or a surface with relatively high gloss, so it is not particularly limited. Those skilled in the art can easily identify and distinguish the smooth surface and the roughened surface of the copper foil. The roughened surface of the copper foil is used for bonding with the base film and the substrate, so the interlayer insulating material of the multilayer substrate is required to have high adhesion to the remaining smooth surface.
[0060] <Resin Layer>
[0061] The resin layer (one or more layers) contained in the present multilayer structure is a resin layer selected from polyimide (PI), liquid crystal polymer (LCP), polyphenylene ether (PPE), multifunctional aromatic vinyl resin (ODV), epoxy resin, or the same resin (composition) as the above-mentioned insulating layer. Generally speaking, it is a constituent element of the substrate constituting a part of the multilayer structure, and is bonded to the roughened surface of the copper foil, and is not bonded to the smooth surface of the copper foil, or is not bonded to the copper foil at all, thereby distinguishing it from the above-mentioned insulating layer. Here, the situation where the present resin layer has the same composition as the above-mentioned insulating layer means that the present resin layer "contains an olefin-aromatic vinyl compound-aromatic polyene copolymer and a surface modifier" in the same manner as the insulating layer. The thickness of the present resin layer is arbitrary, preferably 10μm to 1mm. In addition, from the viewpoint of improving the strength of the structure and reducing the linear expansion coefficient (CTE), the resin layer preferably contains reinforcing materials such as fillers and glass cloth. One surface of the resin layer can be bonded to the roughened surface of the copper foil in advance. The polyimide (PI) mentioned above is a concept including a modified polyimide (MPI) having a further reduced dielectric constant, dielectric loss tangent, and water absorption. The polyphenylene ether mentioned above is preferably a curable PPE having a functional group.
[0062] <Preferred Structure>
[0063] In a preferred embodiment, part or all of the multilayer structure has Figure 1 The basic unit shown in the figure, or its repeated structure, may further have the aforementioned insulating layer, resin layer, or copper foil. As a specific example, it may be composed of Figure 2 , Figure 3 It is formed by one or a combination of the structures (1) to (5) shown.
[0064] In a certain embodiment, part or all of the above basic units can be replaced by Figure 4 In addition, in a certain embodiment, part or all of the above structures (1) to (5) can be replaced by Figure 4A variation of the basic unit shown. That is, it means that at least one surface of the insulating layer may have a recessed portion in the stacking direction, and the copper foil is bonded in such a way that the copper foil is accommodated in the recessed portion, so that a part of the surface is bonded to the smooth surface of the copper foil, and another part of the surface is bonded to the resin layer. That is, as described above, a structure in which the resin layer and the insulating layer are partially directly bonded can be adopted. Such replacement can be carried out, for example, by removing a part of the copper foil by etching and replacing the part with an insulating layer. In other words, the area of each layer contained in the multilayer structure may not be constant, for example, it means that it can be divided into an island shape, or a recess is set. In addition, one or more of the layers of the multilayer structure may have a through hole or a via hole (perforation, internal through hole, blind hole, buried hole, etc.), but in this specification, these holes are not considered in terms of the definition of the layer structure of the multilayer structure (the above-mentioned drawings are depicted in a manner that omits the existence of holes).
[0065] <Insulation layer>
[0066] The thickness of the insulating layer included in the present multilayer structure is arbitrary, generally 1μm to 500μm, preferably 5μm to 100μm. The composition constituting the insulating layer included in the present multilayer structure comprises an olefin-aromatic vinyl compound-aromatic polyene copolymer as its main component, and further preferably comprises a surface modifier (preferably a silane coupling agent) of 0.01 to 5 parts by mass relative to 100 parts by mass of the olefin-aromatic vinyl compound-aromatic polyene copolymer. For the insulating layer, at least a portion thereof is in contact with the smooth surface of the copper foil. In the case where there are multiple layers of the insulating layer, at least one surface of all the insulating layers thereof is in contact with the smooth surface of the copper foil (in other words, in the case of having multiple insulating layers, each is in contact with the smooth surface of the copper foil). In a certain embodiment, it is preferred that any surface of the insulating layer is not bonded to the roughened surface of the copper foil. The composition may contain 30% or more of the olefin-aromatic vinyl compound-aromatic polyene copolymer, preferably 50% or more, more preferably 70% or more of the olefin-aromatic vinyl compound-aromatic polyene copolymer, relative to the entire composition. The olefin-aromatic vinyl compound-aromatic polyene copolymer can be obtained by copolymerizing the monomers of the olefin, the aromatic vinyl compound, and the aromatic polyene.
[0067] The so-called olefin monomer is one or more selected from alpha olefins with a carbon number of 2 or more and 20 or less and cyclic olefins with a carbon number of 5 or more and 20 or less, and is a compound substantially free of oxygen, nitrogen, and halogen and composed of carbon and hydrogen. As alpha olefins with a carbon number of 2 or more and 20 or less, for example, ethylene, propylene, 1-butene, 1-hexene, 1-octene, 1-decane, 1-dodecane, 4-methyl-1-pentene, and 3,5,5-trimethyl-1-hexene can be exemplified. As cyclic olefins with a carbon number of 5 or more and 20 or less, norbornene and cyclopentene can be exemplified. It is preferred that olefins be used as a combination of ethylene and alpha olefins other than ethylene, cyclic olefins, or ethylene alone. In the case where the mass ratio of ethylene alone or the alpha olefin component / ethylene component contained other than ethylene is preferably less than 1 / 7, and more preferably less than 1 / 10, it is preferred that the bonding strength between the obtained solidified body and copper foil and copper wiring can be improved. More preferably, the content of the α-olefin monomer component other than ethylene contained in the copolymer is 6% by mass or less, and most preferably 4% by mass or less, or the olefin is ethylene alone. In addition, in the preferred combination of ethylene and α-olefin other than ethylene, the glass transition temperature of the finally obtained cured product of the ethylene-α-olefin-aromatic vinyl compound-aromatic polyene copolymer can be freely adjusted within the range of about -60°C to -10°C by the type and content of the α-olefin.
[0068] The aromatic vinyl compound monomer is an aromatic vinyl compound having 8 or more and 20 or less carbon atoms, and examples thereof include styrene, p-methylstyrene, p-isobutylstyrene, various vinylnaphthalenes, and various vinylanthracenes.
[0069] As an aromatic polyene monomer, it is a polyene with a carbon number of 5 or more and 20 or less having multiple vinyl and / or vinylidene groups in its molecule, preferably various divinylbenzenes at ortho, meta, and para positions or mixtures thereof, divinylnaphthalene, divinylanthracene, p-2-propylene styrene, p-3-butylene styrene, etc. having an aromatic vinyl structure and substantially containing no oxygen, nitrogen, or halogen and being composed of carbon and hydrogen. In addition, difunctional aromatic vinyl compounds such as 1,2-bis(vinylphenyl)ethane (abbreviated as: BVPE) described in Japanese Patent Publication No. 2004-087639 can also be used. Among them, various divinylbenzenes at ortho, meta, and para positions, or mixtures thereof are preferably used, and a mixture of m-divinylbenzene and p-divinylbenzene is most preferably used. In this specification, these divinylbenzenes are recorded as divinylbenzenes. When divinylbenzenes are used as aromatic polyenes, the curing efficiency is high and it is easy to cure during the curing treatment, so it is preferred.
[0070] As each monomer in the above olefin, aromatic vinyl compound, aromatic polyene, it is also possible to contain other olefins comprising polar groups, such as oxygen atoms, nitrogen atoms, etc., aromatic vinyl compounds comprising oxygen atoms, nitrogen atoms, etc., or aromatic polyenes comprising oxygen atoms, nitrogen atoms, etc., the gross mass of these monomers comprising polar groups is preferably less than 10% by mass of the gross mass of this composition, more preferably less than 3% by mass, most preferably not containing the monomer comprising polar groups. By being set to less than 10% by mass, it is possible to improve the dielectric properties (low dielectric constant / low dielectric loss) of the cured body obtained by curing this composition.
[0071] The present olefin-aromatic vinyl compound-aromatic polyene copolymer preferably satisfies any one or more of the following conditions (1) to (4), and more preferably satisfies all of them.
[0072] (1) The number average molecular weight of the copolymer is 500 or more and less than 100,000.
[0073] (2) The aromatic vinyl compound monomer is an aromatic vinyl compound having 8 to 20 carbon atoms, and the content of the aromatic vinyl compound monomer unit is 0 to 98% by mass, preferably 0 to 70% by mass.
[0074] (3) The aromatic polyene is one or more selected from polyenes having a carbon number of 5 to 20 and having a plurality of vinyl and / or vinylidene groups in the molecule, and the content of vinyl and / or vinylidene groups derived from the aromatic polyene unit is 1.5 to less than 20 per unit number average molecular weight.
[0075] (4) The olefin is one or more selected from olefins having 2 to 20 carbon atoms, the content of the olefin monomer unit is 10% by mass or more, and the total of the olefin monomer unit, the aromatic vinyl compound monomer unit and the aromatic polyene monomer unit is 100% by mass.
[0076] The number average molecular weight (Mn) of the copolymer may be 500 or more and less than 100,000. In the present invention, the number average molecular weight of 500 or more and less than 100,000 means that the molecular weight calculated in terms of standard polystyrene obtained by GPC (gel permeation chromatography) falls within this range.
[0077] The content of the aromatic vinyl compound monomer unit contained in this copolymer can be 0 mass % or more and 98 mass % or less, more preferably 0 mass % or more and 70 mass % or less, and most preferably 10 mass % or more and 60 mass % or less. When the content of the aromatic vinyl compound monomer unit is 70 mass % or less, the glass transition temperature of the cured body of the composition finally obtained becomes lower than the temperature near room temperature, and the toughness and elongation at low temperature can be improved, so it is preferred. If the content of the aromatic vinyl compound monomer unit is 10 mass % or more, the following effect can be obtained: the aromaticity of this copolymer is improved, and the affinity with flame retardant and filler becomes good, and the exudation of flame retardant can be avoided, and the filling property of filler can be improved. In addition, if the content of the aromatic vinyl compound monomer unit is 10 mass % or more, the cured body of the composition with high bonding strength with copper foil and copper wiring can also be obtained.
[0078] In the present copolymer, the content of vinyl and / or vinylidene groups (preferably the content of vinyl groups) derived from the aromatic polyene units can be 1.5 or more and less than 20, preferably 2 or more and less than 20, and most preferably 3 or more and less than 20, based on the unit number average molecular weight. If the content of the vinyl and / or vinylidene groups is 1.5 or more, the crosslinking efficiency becomes high, and a cured product with a sufficient crosslinking density can be obtained. The vinyl content derived from the aromatic polyene units (divinylbenzene units) in the copolymer based on the unit number average molecular weight can be obtained by comparing the number average molecular weight (Mn) calculated by the GPC (gel permeation chromatography) method known to those skilled in the art and the number average molecular weight (Mn) calculated by the standard polystyrene conversion method. 1 The vinyl content derived from the aromatic polyene unit obtained by H-NMR measurement is compared. 1 Comparison of the intensity of each peak area obtained by H-NMR measurement shows that the vinyl content from the aromatic polyene unit (divinylbenzene unit) in the copolymer is 0.45% by mass, and the number average molecular weight based on standard polystyrene conversion measured by GPC is 36,000. The molecular weight of the vinyl from the aromatic polyene unit in this number average molecular weight is the product of these, i.e., 162, which is divided by the formula weight of the vinyl, 27, to obtain 6.0. That is, the vinyl content from the aromatic polyene unit per unit number average molecular weight in this copolymer can be calculated to be 6.0. Utilization of Copolymers 1 The attribution of the peaks obtained by H-NMR measurement is known from the literature. 1 A method for determining the composition of a copolymer by comparing the peak areas obtained by H-NMR measurement is also known. 1 The H-NMR determination method adds the 13The peak area and ratio of the C-NMR spectrum are used to improve the accuracy of the composition. 1 The content of divinylbenzene units in the copolymer was determined by 1H-NMR measurement. That is, based on the content of vinyl groups derived from divinylbenzene units, the content of divinylbenzene units was determined assuming that one vinyl group was derived from one divinylbenzene unit in the copolymer.
[0079] In this copolymer, the content of the preferred olefin monomer unit is 10% by mass or more, more preferably 20% by mass or more, and most preferably 30% by mass or more. The total of the aforementioned olefin monomer unit, the aromatic vinyl compound monomer unit and the aromatic polyene monomer unit is 100% by mass. If the content of the olefin monomer unit is 10% by mass or more, the toughness (elongation) and impact resistance of the cured product finally obtained are improved, and the rupture of the cured product in the midway of curing and the rupture of the cured product in the thermal cycle test are not easy to occur. In this copolymer, the content of the preferred olefin monomer unit is 90% by mass or less.
[0080] For the purpose of obtaining the desired physical properties, the copolymer may be a mixture of a plurality of copolymers. Among the copolymers, olefin-aromatic polyene copolymers not containing an aromatic vinyl compound monomer unit, specifically, ethylene-divinylbenzene copolymers, ethylene-propylene-divinylbenzene copolymers, ethylene-1-butene-divinylbenzene copolymers, ethylene-1-hexene-divinylbenzene copolymers, and ethylene-1-octene-divinylbenzene copolymers can be exemplified as preferred examples.
[0081] In the present copolymer, examples of the olefin-aromatic vinyl compound-aromatic polyene copolymer containing an aromatic vinyl compound monomer unit include ethylene-styrene-divinylbenzene copolymer, ethylene-propylene-styrene-divinylbenzene copolymer, ethylene-1-hexene-styrene-divinylbenzene copolymer, and ethylene-1-octene-styrene-divinylbenzene copolymer.
[0082] <Surface Modifier>
[0083] The composition of the present invention contains a surface modifier for the purpose of improving adhesion to copper foil for wiring. The purpose is especially to improve the bonding strength (peel strength) to the smooth surface of the copper foil. The amount (content) of the surface modifier used is preferably 0.001 to 10 parts by mass, more preferably in the range of 0.01 to 5 parts by mass, and most preferably in the range of 0.01 to 1 part by mass, relative to 100 parts by mass of the olefin-aromatic vinyl compound-aromatic polyene copolymer. If the amount of the surface modifier used is less than 10 parts by mass, the dielectric constant and dielectric loss tangent of the cured body obtained from the composition become low, meeting the purpose of the present invention.
[0084] In the present invention, known surface modifiers can be used. As such surface modifiers, silane-based surface modifiers (also known as silane coupling agents), titanate-based surface modifiers, and isocyanate-based surface modifiers can be cited, and silane-based surface modifiers are preferably used. These surface modifiers can use one or more. Such silane-based surface modifiers can be obtained from Shin-Etsu Chemical Co., Ltd., Dow Corning, and Evonik. Silane-based surface modifiers are silane compounds having functional groups and hydrolysis-condensation groups in the molecule. As functional groups, vinyl, methacryloyloxy, acryloxy, styryl and other vinyls, amino, epoxy, mercapto, thioether, isocyanate, halogen, etc. can be exemplified. Considering the high adhesion to glass, as a functional group, it is preferably selected from one or more of vinyl, amino, epoxy, methacryloyloxy, and acryloxy, and most preferably selected from one or more of amino, methacryloyloxy, and epoxy. These functional groups can have one or more in the molecule. These surface modifiers can be used alone or in combination. As silane-based surface modifiers having a vinyl group as a functional group, for example, vinyl trimethoxy silane and vinyl triethoxy silane can be exemplified. As a silane coupling agent having a styryl group as a functional group, p-styryl trimethoxy silane can be exemplified. As a silane coupling agent having an acryloxy group as a functional group, 3-acryloxy propyl trimethoxy silane can be exemplified. As a silane coupling agent having a methacryloxy group as a functional group, 3-methacryloxy propyl trimethoxy silane, 3-methacryloxy propyl triethoxy silane, 3-methacryloxy propyl methyl dimethoxy silane, and 3-methacryloxy propyl methyl diethoxy silane can be exemplified. Examples of the silane coupling agent having an epoxy group as a functional group include 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane. As silane coupling agents having an amino group as a functional group, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropylethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldiethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropyltriethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, bis(3-trimethoxysilylpropyl)amine, bis(3-triethoxysilylpropyl)amine, and N-(n-butyl)-3-aminopropyltrimethoxysilane can be exemplified. The above are examples of methoxy and ethoxy groups as hydrolytic condensation groups, but triisopropoxy and acetoxy groups can also be used.It is particularly preferable to use a silane-based surface modifier having one or more functional groups selected from a methacryloxy group, an acryloxy group, a vinyl group such as a styryl group, an amino group, an epoxy group, and a mercapto group.
[0085] The preparation of the composition containing the above copolymer and the surface modifier (hereinafter also referred to as "composition") can be carried out as follows. When the copolymer component is in a resinous state, these surface modifiers can be mixed using a known kneading method, such as a twin-screw kneader, various rolls, various kneading machines, etc. When the copolymer component is in a varnish state, it can be mixed and dissolved by adding it to the varnish and stirring.
[0086] The composition of the present invention may contain, in addition to the aforementioned copolymer and surface modifier, one or more selected from the following (a) to (c): (a) a curing agent; (b) one or more resins selected from hydrocarbon elastomers, polyphenylene ether resins, and aromatic polyene resins; (c) a polar monomer.
[0087] <(a) Curing agent>
[0088] As a curing agent that can be used in the composition of the present invention, a known free radical generator and curing agent that can be used in the polymerization or curing of aromatic polyenes and aromatic vinyl compounds can be used. As such a curing agent, free radical polymerization initiators, cationic polymerization initiators, and anionic polymerization initiators can be exemplified, and free radical polymerization initiators can be preferably used. Preferably, organic peroxides (peroxides), azo polymerization initiators, etc. can be freely selected according to the purpose and conditions. The product catalog of organic peroxides can be downloaded from the homepage of NOF Corporation, such as https: / / www.nof.co.jp / business / chemical / chemical-product01. In addition, organic peroxides are also recorded in the product catalogs of FUJIFILM Wako Pure Chemical Corporation and Tokyo Chemical Industry Co., Ltd. The curing agent used in the present invention can be obtained from these companies. In addition, known photopolymerization initiators using light, ultraviolet rays, and radiation can also be used as curing agents. As a curing agent using a photopolymerization initiator, a photoradical polymerization initiator, a photocationic polymerization initiator, or a photoanionic polymerization initiator can be cited. Such a photopolymerization initiator can be obtained from, for example, Tokyo Chemical Industry Co., Ltd. In addition, the curing may be performed by radiation or electron beam itself. In addition, the curing agent may not be included, and the heat of the included raw materials may be used for crosslinking and curing.
[0089] The amount of the curing agent used is not particularly limited, and is generally preferably 0.01 to 10 parts by mass relative to 100 parts by mass of the composition. The composition preferably excludes the curing agent and the solvent. When using a curing agent such as a peroxide or an azo polymerization initiator, the curing treatment is performed at an appropriate temperature and time in consideration of its half-life. The conditions in this case are arbitrary depending on the curing agent, and generally, a temperature range of about 50°C to 200°C is appropriate.
[0090] The varnish of the present invention may contain the total amount of component (b), i.e., "one or more resins selected from hydrocarbon elastomers, polyphenylene ether resins, and aromatic polyene resins" in the range of preferably 1 to 200 parts by mass relative to 100 parts by mass of the copolymer. By adding these components (b), the mechanical properties of the cured product obtained from the varnish can be improved.
[0091] <Hydrocarbon-based elastomer>
[0092] The amount of hydrocarbon elastomer used in the composition of the present invention is preferably 1 to 200 parts by mass, more preferably 1 to 100 parts by mass, and most preferably 1 to 50 parts by mass relative to 100 parts by mass of the copolymer. The number average molecular weight of the hydrocarbon elastomer that can be preferably used in the composition of the present invention is preferably 100 to 100,000 to 4500, more preferably 1000 to 4500. As the hydrocarbon elastomer that can be preferably used in the composition of the present invention, it is preferably selected from one or more elastomers of ethylene-based, propylene-based elastomers, conjugated diene polymers, aromatic vinyl compounds-conjugated diene block copolymers or random copolymers, and their hydrogenates (hydrogenated products). As ethylene-based elastomers, ethylene-octene copolymers, ethylene-1-hexene copolymers and other ethylene-α-olefin copolymers, EPR, EPDM can be cited, and as propylene-based elastomers, atactic polypropylene, low stereoregular polypropylene, propylene-1-butene copolymers and other propylene-α-olefin copolymers can be cited. These hydrocarbon-based elastomers may be modified by introducing a functional group by reacting with a compound such as maleic anhydride.
[0093] As conjugated diene polymers, polybutadiene, 1,2-polybutadiene, etc. can be cited. As block copolymers or random copolymers of aromatic vinyl compounds-conjugated dienes, and their hydrogenated products (hydrogenated products), SBS, SIS, SEBS, SEPS, SEEPS, SEEBS, etc. can be exemplified. 1,2-polybutadiene that can be preferably used can be obtained, for example, from Nippon Soda Co., Ltd. as liquid polybutadiene: product names B-1000, 2000, 3000. In addition, as a copolymer containing a 1,2-polybutadiene structure that can be preferably used, "Ricon100" of TOTAL CRAY VALLEY can be exemplified. These conjugated diene polymers and their hydrogenated products can be modified by introducing functional groups using compounds such as maleic anhydride. One or more resins selected from these hydrocarbon-based elastomers are preferably used in an amount of 150 parts by mass or less, more preferably 1 to 30 parts by mass, and most preferably 1 to 20 parts by mass, based on 100 parts by mass of the copolymer, from the viewpoint of handleability in an uncured state and moldability (handleability as a thermoplastic resin), especially when they are in a liquid state (about 300,000 mPa·s or less) at room temperature (25°C).
[0094] <Polyphenylene ether>
[0095] As the polyphenylene ether (also referred to as "polyphenylene ether resin"), commercially available known polyphenylene ether can be used. The number average molecular weight of the polyphenylene ether is arbitrary, and in consideration of the molding processability of the composition, the number average molecular weight is preferably 10,000 or less, and most preferably 5,000 or less. The number average molecular weight is preferably 500 or more.
[0096] In addition, in the case of addition for the purpose of curing the composition of the present invention, it is preferred that the molecular end is modified by a functional group. In addition, in the case of addition for the purpose of curing the composition of the present invention, it is preferred to have multiple functional groups in one molecule. For example, it is preferably a modified polyphenylene ether. As the functional group, free radical polymerizable functional groups, epoxy groups and other functional groups can be cited, preferably free radical polymerizable functional groups. As a free radical polymerizable functional group, vinyl is preferably used. As a vinyl, it is preferably one or more of the group consisting of allyl, (meth) acryloyl, and aromatic vinyl, more preferably one or more of the group consisting of (meth) acryloyl and aromatic vinyl, and most preferably aromatic vinyl. That is, in the composition of the present invention, it is particularly preferred that the two ends of the molecular chain are modified with free radical polymerizable functional groups. Difunctional polyphenylene ether. As such polyphenylene ether, Noryl (trademark) SA9000 (a modified polyphenylene ether having methacryloyl groups at both ends, with a number average molecular weight of 2200) manufactured by SABIC, a difunctional polyphenylene ether oligomer (OPE-2St, a modified polyphenylene ether having vinyl benzyl groups at both ends, with a number average molecular weight of 1200) manufactured by Mitsubishi Gas Chemical Company, etc. can be cited. In addition, allylated PPE manufactured by Asahi Kasei Corporation can also be used. Among them, the difunctional polyphenylene ether oligomer (OPE-2St) manufactured by Mitsubishi Gas Chemical Company can be preferably used. The amount of the polyphenylene ether used in the composition of the present invention is preferably 1 to 200 parts by mass, more preferably 1 to 100 parts by mass, relative to 100 parts by mass of the copolymer.
[0097] <Aromatic polyene resin>
[0098] The so-called aromatic polyene resin includes a divinylbenzene reactive multi-branch copolymer (PDV, ODV) made by NIPPON STEEL Chemical & Material Co., Ltd. Such multi-branch copolymers are, for example, recorded in the document "Synthesis of multifunctional aromatic vinyl copolymers and development of novel IPN-type low dielectric loss materials using them" (Masanao Kawabe et al., Journal of Japan Institute of Electronics Packaging p125-129, Vol. 12 No. 2 (2009)), U.S. Patent No. 8404797 Specification, International Publication No. 2018 / 181842. In addition, as an aromatic polyene resin, an aromatic polyene polymer resin having the above-mentioned aromatic polyene monomer as the main structural unit can also be cited. The amount of the aromatic polyene resin used in the composition of the present invention is preferably 1 to 200 parts by mass, more preferably 1 to 100 parts by mass, and most preferably 1 to 50 parts by mass relative to 100 parts by mass of the copolymer. The use of the amount of the aromatic polyene resin within these ranges is effective for adjusting the mechanical properties of the cured product obtained from the composition, and is preferred because it prevents a decrease in adhesion to other components and a decrease in toughness. If it is less than 200 parts by mass, it does not exhibit brittleness and improves adhesion to other components.
[0099] <(c) Polar Monomer>
[0100] The polar monomer that can be used in the composition of the present invention is preferably less than 100 parts by mass relative to 100 parts by mass of the copolymer. It should be noted that the present composition may not substantially contain monomers. The so-called polar monomer is a monomer having one or more atoms selected from oxygen, nitrogen, phosphorus, and sulfur in the molecule, and the molecular weight of the polar monomer that can be preferably used is preferably less than 5000, more preferably less than 1000, and further preferably less than 500. The polar monomer that can be preferably used in the composition of the present invention is preferably a polar monomer that can be polymerized using a free radical polymerization initiator. As polar monomers, various maleimides, bismaleimides, maleic anhydride, triallyl isocyanurate, glycidyl (meth) acrylate, tri(meth) acryloyl isocyanurate, trimethylolpropane tri(meth) acrylate, etc. can be cited. The maleimides and bismaleimides that can be used in the present invention are described in, for example, International Publication No. 2016 / 114287 and Japanese Patent Publication No. 2008-291227, and can be purchased from, for example, Yamato Kasei Kogyo Co., Ltd., Nippon Kayaku Co., Ltd., and Designer molecules inc. In addition, the bismaleimide resin "SLK" manufactured by Shin-Etsu Chemical Co., Ltd. can also be used. From the viewpoints of solubility in organic solvents, high-frequency characteristics, high adhesion to conductors, and prepreg formability, these maleimide-containing compounds are preferably bismaleimides. From the viewpoints of solubility in organic solvents, high-frequency characteristics, high adhesion to conductors, and prepreg formability, these maleimide-containing compounds can also be used as polyaminobismaleimide compounds. The polyaminobismaleimide compound can be obtained, for example, by the following method: a compound having two maleimide groups at the end is subjected to a Michael addition reaction with an aromatic diamine compound having two primary amino groups in the molecule. In the case where a high crosslinking efficiency is desired to be obtained by a small amount of addition, it is preferred to use a polar monomer having a multifunctional group of more than two functional groups, and examples thereof include bismaleimides, triallyl isocyanurate (TAIC), and trimethylolpropane tri(meth)acrylate. The amount of the polar monomer used in the composition of the present invention is preferably 0.1 to 20 parts by mass, more preferably 0.1 to 10 parts by mass, relative to 100 parts by mass of the copolymer. By using the amount in this range, the dielectric constant and dielectric loss tangent of the obtained cured body can be obtained without excessively increasing, for example, the dielectric constant can be suppressed to less than 4.0, preferably less than 3.0, and the dielectric loss tangent can be suppressed to less than 0.005, preferably less than 0.002.
[0101] In addition, the composition of the present invention may also be appropriately added with the aforementioned "aromatic vinyl compounds" such as styrene, the aforementioned "aromatic polyenes" such as divinylbenzene, and "aromatic vinylidene compounds" as needed. The amount of addition thereof is arbitrary, but preferably 100 parts by mass or less relative to 100 parts by mass of the copolymer. It should be noted that aromatic vinylidene compounds refer to compounds having a single aromatic ring or a plurality of condensed aromatic rings having 9 to 30 carbon atoms and vinylidene at the same time. As such aromatic vinylidene compounds, indenes, β-substituted styrenes, acenaphthenes, etc. may be cited. As indenes, indenes, various alkyl-substituted indenes, phenyl-substituted indenes, etc. may be cited. As β-substituted styrenes, β-alkyl-substituted styrenes such as β-methyl styrene, or phenyl-substituted styrenes may be cited. As acenaphthenes, acenaphthenes, various alkyl-substituted acenaphthenes, various phenyl-substituted acenaphthenes, etc. may be cited. As aromatic vinylidene compounds, the compounds exemplified above may be used alone, or two or more may be used in combination. The aromatic vinylidene compound is preferably a compound having a boiling point of 175° C. or higher at normal pressure. From the viewpoint of industrial availability and radical polymerizability, acenaphthylene is most preferred as the aromatic vinylidene compound.
[0102] The composition of the present invention may further comprise one or more selected from (d) a filler and (e) a flame retardant.
[0103] <Filling Agent>
[0104] As required, known inorganic or organic fillers can be added. These fillers are added for the purpose of controlling the coefficient of thermal expansion, controlling thermal conductivity, and reducing the price, and their usage amount is arbitrary according to the different purposes. Especially when adding inorganic fillers, known surface modifiers, such as silane coupling agents, etc. are preferably used. Especially in the case of one of the purposes of the present invention, i.e., with a composition having low dielectric constant and low dielectric loss as the purpose, as an inorganic filler, it is preferably one or more of boron nitride (BN) or silicon dioxide, more preferably silicon dioxide. As silicon dioxide, fused silica is preferably used. From the viewpoint of low dielectric properties, if a large amount of addition is carried out, the dielectric constant becomes particularly high, therefore, relative to 100 parts by mass of copolymer, it is preferred to use a filler less than 500 parts by mass, and it is further preferred to use a filler less than 400 parts by mass. In addition, in order to improve and improve low dielectric properties (low dielectric constant, low dielectric loss tangent), a hollow filler and a filler with many shapes of voids can be added.
[0105] The average particle size (d50) of the filler is preferably 0.01 to 100 μm, more preferably 0.1 to 10 μm, and most preferably 0.3 to 1 μm. d50 is a value at which the cumulative volume is 50%. The average particle size (d50) can be obtained from a volume particle size distribution curve obtained by a laser diffraction particle size analyzer (Beckman Coulter "Model LS-230").
[0106] The specific surface area is preferably 1 to 30 m 2 / g, more preferably 3 to 10 m 2 / g.
[0107] The specific surface area can be measured by the following method. 1 g of sample is placed in a measuring cell, and the specific surface area is measured using a Macsorb HM model-1201 fully automatic specific surface area measuring device (BET single point method) manufactured by Mountech. The degassing conditions before the measurement are 200°C-10 minutes. The adsorbed gas is nitrogen.
[0108] The volume ratio of the resin component to the filler is in the range of 98-15:2-85, preferably in the range of 85-15:15-85, more preferably in the range of 85-30:15-70, and even more preferably in the range of 80-60:20-40.
[0109] In addition, organic fillers such as high molecular weight polyethylene or ultra high molecular weight polyethylene can also be used to replace inorganic fillers. For organic fillers, from the viewpoint of heat resistance, it is preferred that they themselves are cross-linked, preferably in the form of particles or powders. These organic fillers can suppress the rise of dielectric constant and dielectric loss tangent.
[0110] On the other hand, by mixing and dispersing a high dielectric constant insulator filler having a dielectric constant of preferably 4 to 10,000, more preferably 5 to 10,000 at 1 GHz in the composition of the present invention, an insulating solidified body having a high dielectric constant insulating layer having a dielectric constant of preferably 4 to 20 and suppressing the increase of dielectric loss tangent (dielectric loss) can be produced. By increasing the dielectric constant of the film formed by the insulating solidified body, the miniaturization of the circuit and the high capacity of the capacitor can be achieved, which can contribute to the miniaturization of high-frequency electrical components. The insulating layer with a high dielectric constant and a low dielectric loss tangent is suitable for use in capacitors, inductors for resonant circuits, filters, antennas, etc. As the high dielectric constant insulator filler used in the present invention, inorganic fillers or metal particles subjected to insulation treatment can be cited. Specific examples are known high dielectric constant inorganic fillers such as barium titanate and strontium titanate, and other examples are specifically described in, for example, Japanese Patent Publication No. 2004-087639.
[0111] <Flame retardant>
[0112] In the composition of the present invention, a flame retardant can be used. From the viewpoint of maintaining a low dielectric constant and a low dielectric loss tangent, a preferred flame retardant is one or more selected from organic phosphorus-based flame retardants such as phosphate esters or their condensates, bromine-based flame retardants, and red phosphorus. In particular, among phosphate esters, compounds having multiple xylene groups in the molecule are preferred from the viewpoint of flame retardancy and low dielectric loss tangent.
[0113] Furthermore, in addition to the flame retardant, as a flame retardant aid, antimony compounds such as antimony trioxide, antimony tetroxide, antimony pentoxide, sodium antimonate, or nitrogen-containing compounds such as melamine, triallyl-1,3,5-triazine-2,3,4-(1H,3H,5H)-trione, and 2,4,6-triallyloxy-1,3,5-triazine can also be added. Relative to 100 parts by mass of the composition, the total amount of these flame retardants and flame retardant aids is usually preferably 1 to 100 parts by mass. In addition, relative to 100 parts by mass of the flame retardant, 30 to 200 parts by mass of the aforementioned polyphenylene ether (PPE)-based resins with low dielectric constants and excellent flame retardancy can be used.
[0114] The composition of the present invention may further contain (f) a solvent. Among the compositions of the present invention, a composition that is particularly liquid due to the inclusion of a solvent is referred to as a varnish.
[0115] <Solvent>
[0116] For the composition of the present invention, a suitable solvent can be added as needed. In addition, its usage amount is not particularly limited. The solvent is used to adjust the viscosity and fluidity of the composition. In particular, when the composition of the present invention is in the form of a varnish, a solvent is preferably used. As a solvent, when the boiling point at atmospheric pressure is too low, that is, when the volatility is too high, there is a concern that the thickness of the coated film becomes uneven, so a solvent with a boiling point above a certain degree is preferred. The preferred boiling point is about 100°C or more at atmospheric pressure, and more preferably 110°C or more and 300°C or less. As a solvent, for example, cyclohexane, toluene (boiling point of 110°C), ethylbenzene, xylene, mesitylene, tetralin, acetone, limonene, mixed alkanes, mixed aromatic solvents, etc. can be used. The usage amount of the solvent used in the composition of the present invention is arbitrary, and is preferably 5 to 500 parts by mass, more preferably 10 to 300 parts by mass, and most preferably 50 to 150 parts by mass relative to 100 parts by mass of the copolymer.
[0117] The composition and varnish of the present invention may contain additives commonly used for resins, such as antioxidants, weathering agents, light stabilizers, lubricants, compatibilizers, antistatic agents, etc., within the range that does not hinder the effects and purposes of the present invention. The composition and varnish of the present invention can be obtained by mixing, dissolving or melting the aforementioned various additives, and any known method can be used as the mixing, dissolving or melting method.
[0118] <Varnish>
[0119] For the varnish of the present invention, by adjusting the composition and molecular weight of the copolymer used, adding a certain amount of liquid monomers, solvents or liquid flame retardants within the scope of the present invention, it can be displayed as a viscous liquid under the conditions of heating at room temperature or below 100°C, for example, at room temperature, it has a viscosity of less than hundreds of thousands of mPa·s, preferably less than 2000mPa·s, more preferably less than 1000mPa·s, and most preferably less than 500mPa·s. Here, the viscosity can be measured, for example, by a rotary viscometer. Specifically, it can be coated, impregnated, filled or dripped into other raw materials using an appropriate method, and the solvent is removed to form a molded body. Furthermore, it is cured by heat and light, so that the target cured body can be obtained. For such properties, various transfer molding (press molding) can be performed, applied to or between substrates, semiconductor device materials, or formed into sheets or films by extrusion lamination or spin coating, and then cured, thereby forming a multilayer structure comprising an insulating layer I.
[0120] <Multilayer structure including insulating layer>
[0121] The molded body of the insulating layer obtained from the composition of the present invention is in the shape of a sheet. Its thickness is arbitrary, but preferably in the range of 10μm to 1mm. These compositions can show the properties of thermoplastic resins. Therefore, it can be formed into a sheet or the like in a substantially uncured state by a known molding method as a thermoplastic resin, such as extrusion molding, injection molding, compression molding, inflation molding, etc., without causing crosslinking, and then can be stacked with other layers and crosslinked (cured). In addition, for example, in the case where the composition is a varnish, after being applied to the smooth surface of other substrates such as copper foil, the solvent can be removed by heating, decompression, air drying, etc. to make a sheet or film-shaped molded body, and then stacked and crosslinked (cured). It is also possible to impregnate the varnish of the present invention into a porous substrate, fabric, or non-woven fabric, remove the solvent, and obtain a composite sheet, which is used as the aforementioned multilayer structure. These sheets can be uncured (semi-cured) to the extent that the sheet shape can be maintained, or they can be fully cured sheets. The degree of curing of the composition can be quantitatively measured using a known dynamic viscoelasticity measurement method (DMA, Dynamic Mechanical Analysis).
[0122] <Curing>
[0123] The curing of the multilayer structure can be performed by known methods with reference to the curing conditions (temperature, time, pressure, light) of the raw materials and curing agent included. When the curing agent used is a peroxide, the curing conditions such as heating conditions can usually be determined with reference to the half-life temperature disclosed for each peroxide.
[0124] <Cured body of multilayer structure>
[0125] The cured body of the multilayer structure of the present invention can be fully cured, and the gel fraction of the cured body of the insulating layer thereof measured in accordance with ASTM can be 90% by mass or more. In addition, for the cured body of the present insulating layer, within the measurement range of 10 to 50 GHz, particularly preferably at 10 GHz, the dielectric constant is preferably 3.0 or less and 2.0 or more, more preferably 2.8 or less and 2.0 or more, and most preferably 2.5 or less and 2.0 or more. The dielectric loss tangent is preferably 0.003 or less and 0.0005 or more, more preferably 0.002 or less and 0.0008 or more. In addition, the volume resistivity of the cured body of the present insulating layer obtained is preferably 1×10 15 When the value is Ω·cm or more and the water absorption is 0.1 mass % or less, it is preferable as an electrical insulating material. These values are particularly preferable values as an electrical insulating material for high frequencies of 3 GHz or more, for example.
[0126] The solidified body of the insulating layer contained in the present multilayer structure also has high adhesion to the smooth surface of the copper foil for wiring. Its bonding strength is preferably more than 0.8N / mm, and more preferably more than 1.0N / mm. Therefore, it is particularly preferably used as an interlayer insulating material and a cover layer. For the interlayer insulating material used in multilayer CCL and FCCL, it is necessary to bond at least a part thereof or at least one side to the smooth surface of the copper foil. The solidified body of the above-mentioned composition shows high adhesion to the smooth surface of the copper foil, so it is preferably used for this purpose. In addition, for the cover layer, it is necessary to bond its lower surface to the smooth surface of the copper foil on the substrate, so it can still be said that the solidified body of the present composition is preferred because it shows high adhesion to the smooth surface of the copper foil.
[0127] As a method for manufacturing a high-frequency transmission line, antenna, and multilayer substrate (CCL, FCCL) having a multilayer structure of the present invention, for example, there is the following method. The following method can be cited: on a substrate (resin layer) having a copper foil smooth surface with an open upper surface by bonding to a copper foil roughened surface, a composition as a varnish is applied, the solvent is removed, and after forming an insulating layer, the surface of other resin layers is further overlapped to form a multilayer structure, and it is treated under appropriate temperature and pressure conditions to be cured and bonded, thereby making a multilayer substrate. Alternatively, the following method can also be exemplified: on a substrate (resin layer) having a copper foil smooth surface with an open upper surface by bonding to a copper foil roughened surface, a pre-made uncured sheet is set as an insulating layer, and the surface of other resin layers is further overlapped to form a multilayer structure, and it is treated under appropriate temperature and pressure conditions to be cured and bonded, thereby making a multilayer substrate.
[0128] As a method for manufacturing a substrate having a covering layer, there is, for example, the following process. The following method can be cited: on a substrate having a copper foil smooth surface with an open upper surface by bonding to a copper foil roughened surface, a composition as a varnish is applied, after the solvent is removed, pressurization and heating are performed under specified conditions to solidify the insulating layer to form a covering layer. Alternatively, the following method can also be exemplified: on a substrate having a copper foil smooth surface with an open upper surface by bonding to a copper foil roughened surface, an uncured sheet of a pre-made composition is overlapped, pressurization and heating are performed, thereby solidifying and bonding the insulating layer.
[0129] From other viewpoints, the present invention is an interlayer insulating material of a cured body comprising the following composition, wherein the composition comprises an olefin-aromatic vinyl compound-aromatic polyene copolymer as a main component, and comprises 0.001 to 10 parts by mass of a silane coupling agent relative to the olefin-aromatic vinyl compound-aromatic polyene copolymer. In addition, the present invention can provide a high-frequency transmission line such as a microstrip line, an antenna, a multilayer CCL substrate or a multilayer FCCL substrate comprising the present interlayer insulating material. The interlayer insulating material layer is an interlayer insulating material in which at least a portion or one of its surfaces is in contact with the smooth surface of the copper foil. The layer formed by the present interlayer insulating material is characterized by good low dielectric properties and heat resistance, and high adhesion to the smooth surface of the copper foil of the substrate.
[0130] From another point of view, the present invention is a covering layer of a cured body comprising the following composition, wherein the composition comprises an olefin-aromatic vinyl compound-aromatic polyene copolymer as a main component and comprises 0.001 to 10 parts by mass of a silane coupling agent relative to the olefin-aromatic vinyl compound-aromatic polyene copolymer, and further, the present invention is a substrate comprising the covering layer. At least the lower surface of the covering layer is in contact with the copper foil smooth surface of the substrate. The covering layer is characterized by the aforementioned good low dielectric properties and heat resistance, and high adhesion to the copper foil smooth surface of the substrate.
[0131] In addition, the insulating layer of the present invention and the bonding of the resin layer as other resin-based materials used in CCL and FCCL can adopt known methods. For example, the method of activating the surface by corona treatment and plasma treatment of the resin layer in advance, the method of forming concave-convex on the surface and roughening it can be exemplified. In addition, the insulating layer formed by the composition of the present invention can show high bonding strength even for each resin of the composition identical with the insulating layer I, such as polyimide (PI), liquid crystal polymer (LCP), polyphenylene ether (PPE), multifunctional aromatic vinyl resin (ODV), epoxy resin or the same as the insulating layer I, and its sheet. Especially in the case where the surface of these resin sheets is treated by surface treatments such as corona treatment and plasma treatment as mentioned above, higher adhesion can be expected.
[0132] Example
[0133] Hereinafter, the present invention will be described by way of examples, but the present invention is not to be construed as being limited to the following examples. The copolymers obtained in the synthesis examples and comparative synthesis examples were analyzed by the following means.
[0134] The content of vinyl units derived from ethylene, hexene, styrene and divinylbenzene in the copolymer is determined by 1 H-NMR was measured based on the intensity of the peak area attributable to each sample. The sample was dissolved in deuterated 1,1,2,2-tetrachloroethane and the measurement was performed at 50 to 130°C.
[0135] The molecular weight was determined by using GPC (gel permeation chromatography) to determine the number average molecular weight (Mn) in terms of standard polystyrene. The measurement was performed under the following conditions.
[0136] Column: Two TSK-GEL MultiporeHXL-M φ7.8×300 mm (manufactured by TOSOH Corporation) were connected in series and used.
[0137] Column temperature: 40°C
[0138] Solvent: THF
[0139] Liquid delivery flow: 1.0ml / min.
[0140] Detector: RI detector
[0141] <Gel Fraction>
[0142] The gel fraction as a boiling toluene insoluble component was determined in accordance with ASTM D2765-84.
[0143] <Water absorption>
[0144] The water absorption rate after immersion in pure water at 23° C. for 24 hours was measured in accordance with ASTM D570-98.
[0145] <Dielectric constant and dielectric loss (dielectric loss tangent)>
[0146] The dielectric constant and dielectric loss tangent were measured at 23° C. and 10 GHz using a cavity perturbation method (8722ES network analyzer manufactured by Agilent Technologies Inc., cavity resonator manufactured by Kanto Electronics Application Development Co., Ltd.) using a 1 mm×1.5 mm×80 mm sample cut out from a sheet.
[0147] <Volume Resistivity>
[0148] The measurement was performed at room temperature using a film having a thickness of about 0.5 mm in accordance with JIS K6911:2006.
[0149] <Adhesion strength (peel strength) between the insulating layer and the smooth surface of the copper foil>
[0150] A copper foil manufactured by Mitsui Mining & Smelting Co., Ltd. (VSP series, TQ-M7-VSP, thickness: 12 μm, surface roughness Rz of the roughened surface: 1.1 μm) was used.
[0151] On a Teflon (registered trademark) sheet, place the copper foil smooth surface upward, overlap several uncured sheets as insulating layer I on the smooth surface, place a SUS mold frame (thickness 0.2 mm) on it, further overlap the Teflon sheet, apply a load of 5 MPa using a press, and heat treat at 120°C for 30 minutes, 150°C for 30 minutes, and then at 200°C for 120 minutes to cure it. Here, the insulating layer I is the uncured sheet of the embodiment and comparative example described later. After curing, remove the Teflon sheet and the mold frame to obtain a multilayer structure in which the sheet and the copper foil are bonded and cured. The bonding strength with the copper foil is measured in accordance with Japanese Industrial Standard (JIS) C6471:1995, and the peeling is evaluated by 180° peeling. For reference, the roughened surface of the copper foil was placed on a Teflon sheet with the roughened surface facing upward, and several uncured sheets were overlapped on the roughened surface to bond and cure to the roughened surface of the copper foil to obtain a laminate, and the bonding strength was measured in the same manner.
[0152] <Production of Copolymer>
[0153] Synthesis Examples P-1, P-2
[0154] With reference to the manufacturing method described in Japanese Patent Publication No. 2009-161743 and Japanese Patent Publication No. 2010-280771, racemic-dimethylmethylenebis(4,5-benzo-1-indenyl)zirconium dichloride (structure see the following formula (1)) as a catalyst, modified methylaluminoxane (Tosoh Finechem, MMAO-3A toluene solution) as a co-catalyst, cyclohexane as a solvent, styrene, divinylbenzene, ethylene, and 1-hexene as required as raw materials were used, and polymerization was carried out using an autoclave with a capacity of 10L, a stirrer and a heating and cooling sleeve. 1-Isopropanol was added to the obtained polymerization solution, and then a large amount of methanol was added to recover the copolymer. The copolymer was air-dried and further vacuum-dried at 30°C for a day and night to obtain copolymers P-1 and P-2. The composition and number average molecular weight of the copolymer are shown in Table 1.
[0155] Formula (1)
[0156] [Chemical formula 1]
[0157]
[0158] Synthesis Example P-3
[0159] With reference to the manufacturing method described in Japanese Patent Laid-Open No. 9-40709, Japanese Patent Laid-Open No. 9-309925, Japanese Patent Laid-Open No. 2009-161743, and Japanese Patent Laid-Open No. 2010-280771, dimethylmethylenebiscyclopentadienyl zirconium dichloride (structure see following formula (2)) as catalyst, modified methylaluminoxane (Tosoh Finechem, MMAO-3A toluene solution) as cocatalyst, cyclohexane as solvent, styrene, divinylbenzene, ethylene as raw materials, and polymerization was carried out using an autoclave with a capacity of 10L, a stirrer, and a heating and cooling sleeve. 1-isopropanol was added to the obtained polymerization solution, and then a large amount of methanol was added to recover the copolymer. The copolymer was thinly spread in a large container and vacuum dried at 30°C for two days and nights. The composition and number average molecular weight of copolymer P-3 are shown in Table 1.
[0160] Formula (2)
[0161] [Chemical formula 2]
[0162]
[0163] In addition, other raw materials are as follows.
[0164] Regarding the difunctional polyphenylene ether oligomer (OPE-2St, number average molecular weight of 1200), the toluene solution product manufactured by Mitsubishi Gas Chemical Company was further diluted with toluene, and a large amount of methanol was further added to precipitate methanol. After air drying, it was dried under reduced pressure to obtain a powdered polyphenylene ether oligomer and used. As 1,2-polybutadiene, "B-3000" manufactured by Nippon Soda Co., Ltd. was used, with a number average molecular weight of 3200 and a viscosity of 210 Poise (21000 mPa·s, 45°C). BMI used BMI-5100 (3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide) manufactured by Yamato Chemical Industry Co., Ltd. The silane coupling agents used were KBM-503 (3-methacryloxypropyltrimethoxysilane), KBM-403 (3-glycidoxypropyltrimethoxysilane), and KBM-1403 (p-phenylvinyltrimethoxysilane) manufactured by Shin-Etsu Silicone Co., Ltd. The curing agent used was Perhexyne 25B (organic peroxide, 2,5-dimethyl-2,5-bis(tert-butylperoxy)-3-hexyne) manufactured by NOF Corporation.
[0165] [Table 1]
[0166]
[0167] [Table 2]
[0168]
[0169] ※1 part by mass was added to 100 parts by mass of the total resin raw materials excluding the curing agent, solvent, silane coupling agent, and filler.
[0170] [Table 3]
[0171]
[0172] ※1 part by mass was added to 100 parts by mass of the total resin raw materials excluding the curing agent, solvent, silane coupling agent, and filler.
[0173] Example 1
[0174] Using a container equipped with a heating and cooling jacket and a stirring blade, P-1 (ethylene-styrene-divinylbenzene copolymer) obtained in the synthesis example, a solvent (toluene), and a silane coupling agent KBM-503 were heated to about 40°C in the proportions shown in Table 2, and the copolymer was dissolved by stirring. Further, 1 part by mass of a curing agent (diisopropylbenzene peroxide) was added to 100 parts by mass of the resin components other than the curing agent, the solvent, and the silane coupling agent, and dissolved, and stirred and mixed to obtain a varnish-like composition. The obtained composition was poured into a silicon mold frame (the frame portion had a length of 7 cm, a width of 7 cm, and a thickness of 0.5 mm, 1.0 mm, or 2.0 mm) on a Teflon sheet set on a glass plate, and after air drying, it was further dried in a vacuum dryer at 60°C for more than 3 hours to obtain an uncured sheet. Furthermore, for the obtained uncured sheet, a Teflon sheet and a SUS mold frame were set under a load of 5 MPa using a press, and heat-treated at 120°C for 30 minutes, 150°C for 30 minutes, and then at 200°C for 120 minutes. The Teflon sheet and the SUS mold frame were removed to obtain a cured sheet.
[0175] Examples 2 to 9, Comparative Examples 1 and 2
[0176] By the same procedure as in Example 1, a curable composition was prepared according to the formulations shown in Table 2 or Table 3 (the units in the table are parts by mass), and uncured sheets and cured sheets of the compositions of Examples and Comparative Examples were obtained by the same procedure.
[0177] Tables 2 and 3 show the gel fraction, dielectric constant, dielectric loss tangent, water absorption, and volume resistivity of the cured sheets.
[0178] In addition, the bonding strength of the interface between the copper foil smooth surface and the cured body of the multilayer structure containing the insulating layer I obtained by the aforementioned method is measured, and the results are shown in Table 2 and Table 3. Here, the insulating layer I is the uncured sheet of the embodiment and the comparative example. In the case of the embodiment, when the bonding strength of the interface between the copper foil smooth surface and the insulating layer I is measured, the bonding strength is too high, showing a value of more than 1N / mm, resulting in the fracture (material rupture) of the resin part, elongation, or the fracture (material rupture) of the copper foil. That is, in these cases, the bonding strength is more than 1N / mm. In contrast, comparative examples 1 and 2 show values of 0.4N / mm and 0.3N / mm respectively. As a reference, the bonding strength of the interface between the roughened surface of the copper foil and the insulating layer I is also measured in the same manner. In all samples of the embodiment and the comparative example, as described above, the bonding strength is shown as more than 1N / mm. That is, the composition involved in the present embodiment can provide a cured body that shows high bonding strength for both the copper foil smooth surface and the roughened surface.
[0179] Example 10
[0180] Using the same apparatus as in Example 1, P-1 (ethylene-styrene-divinylbenzene copolymer) and toluene, silane coupling agent KBM-503, and 1 part by mass of curing agent (dicumyl peroxide) relative to 100 parts by mass of the resin component were added, dissolved, and stirred to obtain a varnish-like composition. Silica filler (SFP-130MC manufactured by Denka Co., Ltd., d50=0.6 μm, specific surface area of 6.2 m 2 / g, density is 2.2g / cm 3 ), stirred to form a slurry varnish. 30 vol% of silica filler was used relative to 70 vol% (volume %) of the resin component. 1 part by mass of the curing agent was added relative to 100 parts by mass of the total resin raw materials excluding the curing agent, solvent, silane coupling agent and filler.
[0181] Embodiment 11
[0182] Made Figure 2 Here, the resin layer A is formed of polyimide, and the insulating layer I and the resin layer B are formed of a composition containing the copolymer of the present invention.
[0183] Prepare a multilayer sheet (commercially available product, Upisel N, polyimide film is 25μm, electrolytic copper foil is 18μm, single-sided copper-clad type) in which the roughened surface of the copper foil is bonded to the polyimide (PI) sheet. Further, prepare an uncured sheet with a thickness of 500μm obtained in the same manner as in Example 10. Copper foil manufactured by Mitsui Mining & Smelting Co., Ltd. (VSP series, TQ-M7-VSP) was used. On the open copper foil smooth surface of the multilayer sheet in which the roughened surface of the copper foil is bonded to the polyimide (PI) sheet, an uncured sheet (insulating layer I) with a thickness of 100μm obtained in the same manner as in Example 5 is placed, and further on the uncured sheet is placed an uncured sheet (resin layer B) with a thickness of 100μm obtained in the aforementioned Example 10, and further on it, copper foil is placed in a manner such that the roughened surface of the copper foil is in contact with the resin layer B. A portion of a thin Teflon sheet was inserted between the smooth surface of the copper foil and the uncured sheet (insulating layer I) of Example 5, and cured under the same conditions as in Example 1 under the conditions of pressurization using a press, to obtain a multilayer structure sheet stacked and bonded in the order of resin layer A (polyimide) / copper foil / insulating layer I / resin layer B (Example 10) / copper foil from the bottom. After curing, the inserted Teflon sheet was pulled out, and the starting point of the tensile test was made, and the bonding strength between the smooth surface of the copper foil and the insulating layer I was obtained. Similarly, a portion of a thin Teflon sheet was inserted between the insulating layer I and the resin layer B, and it was cured in the same way and the bonding strength between the insulating layer I and the resin layer B of the obtained multilayer structure sheet was obtained. Any sample showed a bonding strength of more than 1N / mm, resulting in the breakage (material rupture) and elongation of the resin part, or the breakage (material rupture) of the copper foil. That is, in these cases, the bonding strength between the smooth surface of the copper foil and the insulating layer I, and between the insulating layer I and the resin layer B are all 1N / mm or more. In addition, the bonding strength between the commercially available polyimide (PI) and the roughened surface of the copper foil measured separately is also 1N / mm or more. From the above results, it can be seen that the multilayer structure of the present invention has a strong bonding strength between each interface.
[0184] Example 12
[0185] Made Figure 3The structure (4) shown. Here, the insulating layer I is formed by a composition comprising the copolymer of the present invention, and the resin layers A and B are both formed by polyimide (PI). On the open copper foil smooth surface of a multilayer sheet (commercially available, the same as in Example 11) where the roughened surface of the copper foil is bonded to a polyimide (PI) sheet, an uncured sheet (insulating layer I) having a thickness of 100 μm obtained by the same operation as in Example 6 is placed, and further a multilayer sheet (commercially available) where the roughened surface of the copper foil is bonded to a polyimide (PI) sheet is placed thereon in contact with the open copper foil smooth surface, and cured under the same conditions as in Example 1 under conditions of pressurization using a press, thereby obtaining a multilayer structure sheet in which resin layer A (polyimide) / copper foil / insulating layer I / copper foil / resin layer B (polyimide) is stacked and bonded in the order of from the bottom. As in Example 11, a portion of a thin Teflon sheet was inserted between the smooth surface of the copper foil and the uncured sheet (insulating layer I) of Example 6 before curing, and the thin Teflon sheet was pulled out to make the starting point of the tensile test, and the bonding strength between the smooth surface of the copper foil and the insulating layer I was obtained. As a result, a bonding strength of 1N / mm or more was shown, resulting in a fracture (material rupture) of the resin portion. That is, the bonding strength between the smooth surface of the copper foil and the insulating layer I was 1N / mm or more.
[0186] Embodiment 13
[0187] Made Figure 1 The basic unit structure shown. Here, the insulating layer I is formed by the composition of the copolymer of the present invention, and the resin layer A is polyimide. On the open copper foil smooth surface of the multilayer sheet (commercially available, the same as in Example 11) on which the roughened surface of the copper foil is bonded to the polyimide (PI) sheet, an uncured sheet (insulating layer I) with a thickness of 500 μm obtained in the same manner as in Example 2 is placed, and a portion of the thin Teflon sheet is inserted between the copper foil smooth surface and the uncured sheet (insulating layer I), and the same conditions are used to cure and bond under the same conditions as in Example 1 under the conditions of pressurization using a press to obtain a cured sheet of a multilayer structure formed by resin layer A (polyimide) / copper foil / insulating layer I. The inserted Teflon sheet is pulled out, thereby making the starting point of the tensile test, and the bonding strength between the copper foil smooth surface and the insulating layer I is determined. As a result, a bonding strength of more than 1 N / mm is shown, resulting in rupture (material rupture), elongation, or rupture (material rupture) of the resin portion. That is, the bonding strength between the smooth surface and the insulating layer I is 1 N / mm or more.
[0188] Embodiment 14
[0189] Made Figure 1The basic unit structure shown. Copper foil manufactured by Mitsui Mining & Smelting Co., Ltd. (VSP series, TQ-M7-VSP) was used. Here, both the insulating layer I and the resin layer A are formed by the composition of the copolymer of the present invention. On an uncured sheet (resin layer A) having a thickness of 500 μm obtained in the same manner as in Example 10, a copper foil is placed in such a way that the roughened surfaces are in contact, and an uncured sheet (insulating layer I) having a thickness of 500 μm obtained in the same manner as in Example 2 is further placed on the smooth surface, and a portion of a thin Teflon sheet is inserted between the smooth surface of the copper foil and the uncured sheet (insulating layer I), and the same conditions are used to perform curing and bonding under the conditions of pressurization using a press as in Example 1, to obtain a cured sheet having a multilayer structure formed by resin layer A (Example 10) / copper foil / insulating layer I. The inserted Teflon sheet is pulled out, thereby making the starting point of the tensile test, and the bonding strength between the smooth surface of the copper foil and the insulating layer I is determined. As a result, an adhesive strength of 1 N / mm or more is shown, resulting in fracture (material rupture) and elongation of the resin portion or fracture (material rupture) of the copper foil. That is, the adhesive strength between the smooth surface and the insulating layer I is 1 N / mm or more.
[0190] The cured body of the insulating layer formed by the composition of the present invention shows a high gel fraction, is fully cured, and can show a low dielectric constant, a low dielectric loss tangent, a low water absorption rate, and a high resistivity. The cured body of the multilayer structure of the present invention not only shows high bonding strength to the roughened surface of the copper foil, but also can show high bonding strength to the smooth surface of the copper foil. Therefore, each layer can have high adhesion, and the cured body of the multilayer structure is useful as an interlayer insulating layer (interlayer insulating material) and a covering layer of a high-frequency transmission line, a multilayer CCL, a multilayer FCCL, or an antenna.
Claims
1. A method for producing a multilayer structure, the multilayer structure comprising: More than one insulating layer, One or more resin layers, and One or more copper foils having a smooth surface and a roughened surface, In the multilayer structure, The insulating layer comprises an olefin-aromatic vinyl compound-aromatic polyene copolymer and a surface modifier, The resin layer comprises one or more selected from polyimide (PI), liquid crystal polymer (LCP), polyphenylene ether (PPE), multifunctional aromatic vinyl resin (ODV), epoxy resin, and the same composition as the insulating layer. The manufacturing method comprises: The step of bonding the roughened surface of the first copper foil to at least one surface of the first resin layer so that the smooth surface of the first copper foil and a part of the surface of the first resin layer are in an open state, a step of applying a varnish containing at least the olefin-aromatic vinyl compound-aromatic polyene copolymer to the open smooth surface of the first copper foil and a portion of the surface of the first resin layer, and The step of removing the solvent from the applied varnish and forming a first insulating layer on the smooth surface of the first copper foil and a portion of the surface of the first resin layer.
2. A method for producing a multilayer structure, the multilayer structure comprising: More than one insulating layer, One or more resin layers, and One or more copper foils having a smooth surface and a roughened surface, In the multilayer structure, The insulating layer comprises an olefin-aromatic vinyl compound-aromatic polyene copolymer and a surface modifier, The resin layer comprises one or more selected from polyimide (PI), liquid crystal polymer (LCP), polyphenylene ether (PPE), multifunctional aromatic vinyl resin (ODV), epoxy resin, and the same composition as the insulating layer. The manufacturing method comprises: The step of bonding the roughened surface of the first copper foil to at least one surface of the first resin layer so that the smooth surface of the first copper foil and a part of the surface of the first resin layer are in an open state, a step of preparing an uncured sheet comprising at least the olefin-aromatic vinyl compound-aromatic polyene copolymer, and The step of providing the uncured sheet on the open smooth surface of the first copper foil and a portion of the surface of the first resin layer to form a first insulating layer.
3. The manufacturing method according to claim 1 or 2, further comprising the step of forming a second resin layer that is not bonded to any copper foil. 4 . The manufacturing method according to claim 1 , further comprising the step of removing a portion of the first copper foil by etching so that the smooth surface of the first copper foil and a portion of the surface of the first resin layer are in an open state.
5. The production method according to any one of claims 1 to 4, wherein The surface modifier is a silane coupling agent.
6. The production method according to any one of claims 1 to 5, wherein The olefin-aromatic vinyl compound-aromatic polyene copolymer satisfies all of the following conditions (1) to (4), (1) The number average molecular weight of the copolymer is 500 or more and less than 100,000; (2) the aromatic vinyl compound monomer is an aromatic vinyl compound having 8 to 20 carbon atoms, and the content of the aromatic vinyl compound monomer unit is 0 to 98% by mass; (3) the aromatic polyene is one or more selected from polyenes having a plurality of vinyl and / or vinylidene groups in the molecule and having a carbon number of 5 to 20, and the content of vinyl and / or vinylidene groups derived from the aromatic polyene unit is 1.5 to less than 20 per unit number average molecular weight; (4) The olefin is one or more selected from olefins having 2 to 20 carbon atoms, the content of the olefin monomer unit is 10% by mass or more, and the total of the olefin monomer unit, the aromatic vinyl compound monomer unit and the aromatic polyene monomer unit is 100% by mass. 7 . A method for producing a cured multilayer structure, comprising the step of curing the multilayer structure obtained by the production method according to claim 1 .
8. The manufacturing method according to claim 7, wherein: The curing includes a step of applying heat and / or pressure.
Citation Information
Patent Citations
Copper-clad laminate, wiring board, and copper foil provided with resin
CN112789167A
Laminate, method for manufacturing laminate, multilayer printed wiring board and semiconductor device
JP2009166404A
Metal foil with adhesive layer, metal-clad laminate, and printed wiring board and multilayer wiring board obtained by using the metal-clad laminate
JP2012227534A
Copper clad laminate, printed circuit board, and method of manufacturing the same
US20150021084A1
Copolymer and laminate containing same
WO2021112087A1
